Le Parc Méric à Montpellier : représentations sociales d’un parc public entre campagne, jardin et nature sauvage - Gaëlle Aggéri (Développement Durable et Territoires)
Motivated by the desire to use ecological engineering methods and of offering city dwellers a variety of green spaces ranging from the traditional sophisticated garden to “wild” open spaces, the directors of municipal parks and green spaces have experimented with what is called in France “La gestion différenciée” or “the differentiated management” of green spaces.Parallel with this essentially technical approach, the evolution of the idea of “urban nature”, demanded by the directors of municipal parks and green spaces, brought about the creation of alternative public parks, whose image and use refer strongly to the pastoral and “the wild”.This study investigates the physical and symbolic construction of this new type of nature, in particular with the example of the design and the social representations of the “Parc Méric” in Montpellier, a former bourgeois rural estate. The hypothesis we wish to check is that the public of this public park will share the same simultaneously environmental and artistic paradoxical references as the local authorities who designed and managed it.